2018
DOI: 10.1097/mol.0000000000000503
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs in lipid metabolism

Abstract: Purpose of review Noncoding RNAs have emerged as important regulators of cellular and systemic lipid metabolism. In particular, the enigmatic class of long noncoding RNAs have been shown to play multifaceted roles in controlling transcriptional and posttranscriptional gene regulation. In this review, we discuss recent advances, current challenges and future opportunities in understanding the roles of lncRNAs in the regulation of lipid metabolism during health and disease. Recent findings Despite comprising t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 65 publications
0
47
0
Order By: Relevance
“…[1][2][3][4] Hepatic lipid metabolism is tightly regulated through a delicate interplay of hormones (such as insulin), nuclear receptors (such as LXR), numerous cellular signalling pathways (such as PI3K/AKT/ mTOR) and hepatic transcription factors (such as MLXIPL/ChREBP and SREBPs). [12][13][14][15] In this study, we investigated the role of lncRNA H19 in regulating hepatic lipid metabolism. Emerging evidence suggests that non-coding RNAs (ncRNAs), especially long non-coding RNAs (lncRNAs), may play an important role in liver metabolism and metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Hepatic lipid metabolism is tightly regulated through a delicate interplay of hormones (such as insulin), nuclear receptors (such as LXR), numerous cellular signalling pathways (such as PI3K/AKT/ mTOR) and hepatic transcription factors (such as MLXIPL/ChREBP and SREBPs). [12][13][14][15] In this study, we investigated the role of lncRNA H19 in regulating hepatic lipid metabolism. Emerging evidence suggests that non-coding RNAs (ncRNAs), especially long non-coding RNAs (lncRNAs), may play an important role in liver metabolism and metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This is partly through the SREBP transcription factors, which are the master regulators of cellular lipid and cholesterol processes, with SREBP1c preferentially activating the fatty acid synthesis pathway . Recent studies have demonstrated the role of lincRNAs in regulating and helping regulate SREBPs in their functions . For instance, metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1), the nucleus‐specific lincRNA, inhibits degradation of SREBP1c protein by preventing its ubiquitination in the nucleus .…”
Section: Discussionmentioning
confidence: 99%
“…As advances in deep and high‐throughput sequencing have emerged, novel players have been identified in lipid biology, including the identification of a unique group of noncoding genes called long noncoding RNAs (lncRNAs) . LncRNAs are >200 nucleotides long, show tissue and cell‐type specificity, and can differentially regulate signaling pathways .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CYP7A1 as a target gene of LXRs, its low-level expression causes cholesterol catabolism disorder and cholic acid synthesis reduction. Based on the above research results, CYP7A1 signaling has been mentioned to participate in lipid metabolism, and a variety of molecules including LXRα, SREBP-1c, FXR, FAS, 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR), lecithin cholesterol acyltransferase (LCAT), and the scavenger receptor CD36 were involved, and then regulate the dynamic balance of serum TC and TG concentrations through fatty deposition (body fatty and IMF) and oxidative decomposition (Chiang 2003;van Solingen et al 2018;Zhang et al 2018). Thus, different haplotypes may cause the differentiating expression of CYP7A1 lead to the differential expression of genes involved in lipid metabolism, and all of these genes together affect intramuscular fat (IMF) content of chest muscles, percentage of abdominal fat (AFP), serum triglycerides (TG) and total cholesterol (TCH) concentrations.…”
Section: Discussionmentioning
confidence: 99%